The GPI‐anchored Gas and Crh families are fungal antigens - Arroyo, Javier; Sarfati, Jaqueline; Baixench, Marie Thérése; Ragni, Enrico; Guillén, Marivi; Rodriguez‐Peña, José Manuel; Popolo, Laura; Latgé, Jean Paul (Yeast (Chichester, England), 2007)
The cell wall is the first interface between a fungus and its extracellular environment. Glycosyltransferases involved in the formation and dynamic remodelling of the polysaccharide network of the cell wall have recently been identified. The best characterized ones belong to the Gas family, which elongates β(1,3)‐glucans, and to the Crh family, which are involved in the cross‐linking of chitin to β(1,6)‐glucan. All these proteins carry a glycosylphosphatidylinositol (GPI) anchor. In this work, we show that recombinant soluble forms of Gas1–5 and Crh1p from Saccharomyces cerevisiae and their orthologous proteins Gel1‐Gel2 and Crf1 from Aspergillus fumigatus are specifically recognized by antibodies present in the sera of patients with Aspergillus or Candida infections. Quantification of the antibody titres against recombinant Gas/Gel and Crh/Crf proteins separated aspergilloma and candidiasis patients from non‐infected individuals. Cross‐reactivity was seen between the antibody response of patients with aspergillosis and candidiasis towards the Gas/Gel and Crh/Crf proteins. These results suggest that GPI‐anchored cross‐linking enzymes are relevant immunologically reactive constituents of the cell wall that may play a role during human fungal infections. Copyright © 2007 John Wiley & Sons, Ltd.